Economical Catches Landed at Sibolga Fishing Port in 2017 to 2021 - Denta Tirtana; Arie Nurfita; Imam Teguh Santausa; Ayang Armelita Rosalia; Rama Agus Mulyadi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Sibolga fishing port is is a type B port located in the western Sumatran coastal, located in North Sumatra Province. The catch landed by fishermen at PPN Sibolga is included in economically important fish. Data on the types of economically important fish landed at PPN Sibolga have not been identified as a whole. Therefore, this study aims to analyze the total catch, production value, and fish resources that have high economic value landed at Sibolga fishing Port from 2017 to 2021.Primary data collection was obtained from observations and secondary data collected from catch data landed at Sibolga PPN from 2017 to 2021. Primary data collection was obtained from observations and secondary data collected from catch data landed at Sibolga Fishing Port from 2017 to 2021. The total catch landed at Sibolga PPN increased from 2017 to 2018 and decreased from 2018 to 2021. Types of fish that have important economic value in the period 2017 to 2021 include skipjack 57,84% with a value of Rp.1.025.925.917,016, Mackerel scad 21,38% with a value of Rp.379.229.298.642, Yellowfin tuna 12,33% with a value of Rp.218.612.925.700, Frigate tuna 6,56% with a value of Rp.116.292.175.417 and Bentong selar 1,90% with a value of Rp.33.674.972.000.